2017
DOI: 10.18632/oncotarget.19294
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen protects type II collagen in interleukin-1β-induced mandibular condylar chondrocyte via inhibiting the JNK/c-Jun signaling pathway

Abstract: The aim of this study was to explore the mechanisms of Hyperbaric oxygen (HBO) protective on interleukin-1β (IL-1β) induced rat's mandibular condylar chondrocytes. Chondrocytes were exposure to Hyperbaric oxygen after induced inflammatory by IL-1β. After that, the expression of p-JNK and c-Jun was increased significantly, while the Sox-9 was decreased significantly, Immunofluorescence results showed that the expression of p-JNK and p-c-Jun were decreased while the expression of Sox-9 and COL2 were increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…As mentioned in the INTRODUCTION, decreased IL-1␤ following HBO 2 has been observed in other pathological processes (16,17,23,24,44,45,71). This action appears to be beneficial as it diminished IL-1␤-mediated activation of several MAPKs and concurrent increased expression of the extracellular matrix proteins type 2 collagen and aggrecan and the transcription factor Sox-9 in rat chondrocytes (6,43); abrogated radiationinduced increases in TNF-␣ and IL-1␤, along with an HBO 2mediated increase in IL-10 in rat larynx (1); inhibited p38 MAPK activation in rat hippocampal neurons and astrocytes mediated by amyloid ␤ peptide (72); and inhibited increases in TNF-␣ and IL-1␤ with subsequent activation of NF-B, p38, and c-JUN-NH 2 -terminal kinase in postischemic testicular tissue (70) and in isolated human intervertebral nucleus pulposus cells (36).…”
Section: Discussionmentioning
confidence: 95%
“…As mentioned in the INTRODUCTION, decreased IL-1␤ following HBO 2 has been observed in other pathological processes (16,17,23,24,44,45,71). This action appears to be beneficial as it diminished IL-1␤-mediated activation of several MAPKs and concurrent increased expression of the extracellular matrix proteins type 2 collagen and aggrecan and the transcription factor Sox-9 in rat chondrocytes (6,43); abrogated radiationinduced increases in TNF-␣ and IL-1␤, along with an HBO 2mediated increase in IL-10 in rat larynx (1); inhibited p38 MAPK activation in rat hippocampal neurons and astrocytes mediated by amyloid ␤ peptide (72); and inhibited increases in TNF-␣ and IL-1␤ with subsequent activation of NF-B, p38, and c-JUN-NH 2 -terminal kinase in postischemic testicular tissue (70) and in isolated human intervertebral nucleus pulposus cells (36).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated that overexpression of miR-140-3p inhibits the proliferation, migration and invasion of breast cancer cells [31], The present experiment con rmed that overexpressed miR-140 could promote chondrocyte proliferation and migration by CCK-8 assay and scratch assay, and further examined chondrocyte differentiation-related markers including type II collagen, SOX-9 and aggrecan as well as chondrocyte-related gene expression by PCR and Western blot assay, while SOX-9, COL2, ACAN and RUNX2 were important osteogenic and chondrogenic markers [32], upregulation of SOX-9 and COL2 expression was also found to inhibit IL-1β-induced in ammatory responses in chondrocytes [33], It is thus clear that chondrocyte recovery is best facilitated when miR-140 is overexpressed. Pauline Po-Yee Lui et al found that a high percentage of type I collagen may be responsible for poor matrix organization in calci ed tendinopathy [34],type II collagen, on the other hand, plays an indispensable role in chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The sizes of the PCR products and sequences of the forward and reverse primers for each gene analyzed in this study are listed in Table 1. Real-time qPCRs of the reversely transcribed cDNAs were performed by the CFX Connect Real-Time PCR Detection System (Bio-Rad Laboratories, Inc., Hercules, CA) and analyzed by the CFX Manager 3.0 software (Bio-Rad Laboratories, Inc.) using GAPDH as the reference housekeeping gene, given that GAPDH has been widely used as the major reference gene in multiple previous studies about the effects of HBO exposures on gene expression, [111][112][113][114] and our microarray analyses revealed less than ±0.2 in the Log2 fold changes and more than 0.5 in the p values in GAPDH gene expression levels in mouse blastocysts under HBO versus normoxic exposures in vivo.…”
Section: Total Rna Extraction From Mouse Blastocysts and Quantitative...mentioning
confidence: 99%